The Effect of Capital Expenditure on Regional Financial Performance With Local Original Income as an Intervening Variable in Districts and Cities in NTT Province in 2017-2021 - Teresa Ona Delang; Riris Rotua Sitorus (CV. Syntax Corporation Indonesia, 2024)
The research aims to analyze the influence of capital expenditure for local government financial performance through local government revenue as intervening variables. The sampling technique in this study is to use the purposive sampling method. The object of this research is all districts and cities in NTT, with a sample of 22 districts and cities. The data used is a type of secondary data, which was obtained from the realization of the 2017-2021 district and city revenue and expenditure budget (APBD) in NTT. The results of this study indicate that capital expenditures have an influence on local government revenue, and local government revenue has an influence on local government financial performance. Apart from that capital expenditures have a local government financial performance, with all of them having a positive correlation. The local government revenue is able to mediate the relationship between capital expenditures on local government financial performance.